Journalism and public relations: a look from the two sides of the news - Vásquez Chaparro, Hellen (2017)
The purpose of this article is to demonstrate the relationship that exists between journalism and public relations, from a practical point of view and based on the experience of the author. It shows the evolution of Public Relations, as the main connector between the company and the local media, for the dissemination of key messages